PENGARUH PELAYANAN TABUNGAN BAJAPUIK TERHADAP KEPUASAN NASABAH PT. BANK PERKREDITAN RAKYAT GUGUK MAS MAKMUR KECAMATAN GUGUK KABUPATEN 50 KOTA SUMATERA BARAT - Ryan Pratama Putra; Lena Farida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Service is each every activity or action which can on the market by an on the side of other party, what abstract basically and do not result the ownership of any. While Gronroos in Tjiptono ( 2005) expressing that service represent process consisted of to by with refer to abstract activity (ordinary intangible) but do not have to always became of by interaction of among/between customer/ client of employees and, resource and service, goods or physical, and system service, what is provided by as solution for cutomer/ client problem. Hasibuan defining service as service gift activity from an on the side of of other party. good service is done/conducted affablely, is fair quickly, and with good ethics so that comprehend satisfaction and requirement for accepting it. Client satisfaction in principle is complacence got by client of because getting value service, in this case is bank. Assess value can come from product, service, or something that have the character of emotion.This research is done/conducted in Prosperous BPR Guguk Mas, Jl. Tan Malaka Km. 14 Market of Dangung-Dangung of Regency 50 Town. West Sumatra. As for reason chosen BPR Guguk Mas. Target of this Research is conducted to know influence of service to client satisfaction. In this research is methodologies used by is quantitative and descriptive with program SPSS, where sampel used by that is client and as source of information is party HRD, Front of Office and Manager marketing. To determine sampel use formula Slovin, method of sampling by accidental is sampling. Technics of data collecting of through, observation and kuesioner.From result analyse data covering validity test, reabilitas, and linear regresi modestly, quality of service to client satisfaction. Each owning indicator which each other be interconnected and have an effect on positive to satisfaction of client of at in BPR Guguk MasKeyword: service excellent and the Client Satisfaction.